2021
DOI: 10.3389/fnut.2020.628405
|View full text |Cite
|
Sign up to set email alerts
|

LAT1 Protein Content Increases Following 12 Weeks of Resistance Exercise Training in Human Skeletal Muscle

Abstract: Introduction: Amino acid transporters are essential for cellular amino acid transport and promoting protein synthesis. While previous literature has demonstrated the association of amino acid transporters and protein synthesis following acute resistance exercise and amino acid supplementation, the chronic effect of resistance exercise and supplementation on amino acid transporters is unknown. The purpose herein was to determine if amino acid transporters and amino acid metabolic enzymes were related to skeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…In the present study, we did not observe changes in LAT1 protein levels for either 8-week RT protocol. In contrast, we recently reported that skeletal muscle LAT1 protein levels increased in untrained subjects following 12 weeks of RT ( Roberson et al, 2021 ). To our knowledge, this is the first study to investigate the chronic effects of RT on LAT1 in resistance-trained individuals.…”
Section: Discussionmentioning
confidence: 87%
“…In the present study, we did not observe changes in LAT1 protein levels for either 8-week RT protocol. In contrast, we recently reported that skeletal muscle LAT1 protein levels increased in untrained subjects following 12 weeks of RT ( Roberson et al, 2021 ). To our knowledge, this is the first study to investigate the chronic effects of RT on LAT1 in resistance-trained individuals.…”
Section: Discussionmentioning
confidence: 87%
“…This could suggest that membrane bound LAT1 increases only when large amounts of exogenous amino acids are not readily available to muscle fibers. Furthermore, although chronic resistance exercise was shown to elevate LAT1 protein content in whole muscle lysates, membrane associated LAT1 was not affected [50]. As such, available evidence suggests that membrane associated/localized LAT1 is unaffected by both acute and chronic anabolic stimuli.…”
Section: Discussionmentioning
confidence: 88%
“…The metanalysis for FFM was performed on 6 studies [30,31,34,47,56,59]. Based on the results of pooled analysis, WP intake resulted in 0.12 kg increase of FFM, which was not statistically significant (p: 0.50, I 2 : 48.2%, P heterogeneity : 0.08), (Table 2).…”
Section: Fat Free Massmentioning
confidence: 99%